System of methodological actions to improve the preparation of the- directors of the sports institution - Eduardo Pavó-Suárez (Universidad de Guantánamo, 2015)
This work proposes a system of methodological actions to improve the preparation of the work politics of the sports institution of the north area in Guantanamo city, as the best way to get a better efficiency in an administrative action. The scientific problem of this investigation is related to the insufficient preparation that the directors show at this level, especially concerning the mastery of the general functions of directing. Different methods and techniques were used to get a better preparation of the directors of these centres. The methodological action system proposed is characterized mainly for the improving in the practical order of the procedures to increase the level of knowledge, so that they can face in a better way their daily work. The paper´s viability was evaluated through the criteria methods used for corroborating the applicability of the methodological action system to be inserted in the training plans for the political directors at this level.